Excimers in Multichromophoric Assemblies: Boon or Bane? - Chaudhuri, Debangshu (Organic Materials, 2021)
Exciton dynamics in organic semiconductors is a subject of great significance from the standpoint of light emission, as well as light harvesting. As transient excited state species, excimers are expected to play a significant role in the dynamics and the fate of the excited state. Till recently, the discourse on excimers in organic systems revolved around their role in aggregation-induced fluorescence quenching, or utilizing their characteristic red-shifted emission to report local interactions. But in the last decade, research in the area of organic multichromophoric systems has brought the spotlight back on this fascinating species. This review focuses on recent developments that highlight the importance of excimers in various processes involving multichromophoric systems, such as circularly polarized emission, exciton migration, and singlet fission. The review also attempts to address the question of whether excimers are useful or detrimental to various photophysical and photochemical processes of importance.Table of content:IntroductionExcimers in Multichromophoric AssembliesExcimer LuminescenceExcimers in Light HarvestingConclusions and Outlook
Keywords: excimers; multichromophoric assembly; circularly polarized luminescence; exciton migration; singlet fission; symmetry-breaking charge separation